Association of early life physical and sexual abuse with premature mortality among female nurses: prospective cohort study. (3rd May 2023) - Wang, Yi-Xin; Sun, Yang; Missmer, Stacey A; Rexrode, Kathryn M; Roberts, Andrea L; Chavarro, Jorge E; Rich-Edwards, Janet W
Abstract: Objective: To explore associations between early life physical and sexual abuse and subsequent risk of premature mortality (death before age 70 years). Design: Prospective cohort study. Setting: The Nurses' Health Study II (2001-19). Participants: 67 726 female nurses aged 37-54 years when completing a violence victimization questionnaire in 2001. Main outcome measures: Hazard ratios and 95% confidence intervals for total and cause specific premature mortality by childhood or adolescent physical and sexual abuse, estimated by multivariable Cox proportional hazard models. Results: 2410 premature deaths were identified over 18 years of follow-up. Nurses who experienced severe physical abuse or forced sexual activity in childhood and adolescence had a higher crude premature mortality rate than nurses without such abuse in childhood or adolescence (3.15 v 1.83 and 4.00 v 1.90 per 1000 person years, respectively). The corresponding age adjusted hazard ratios for premature deaths were 1.65 (95% confidence interval 1.45 to 1.87) and 2.04 (1.71 to 2.44), respectively, which were materially unchanged after further adjusting for personal characteristics and early life socioeconomic status (1.53, 1.35 to 1.74, and 1.80, 1.50 to 2.15, respectively). Cause specific analyses indicated that severe physical abuse was associated with a greater risk of mortality due to external causes of injury and poisoning (multivariable adjusted hazard ratio 2.81, 95% confidence interval 1.62 to 4.89), suicide (3.05, 1.41 to 6.60), and diseases of the digestive system (2.40, 1.01 to 5.68). Forced sexual activity as a child and adolescent was associated with greater risk of mortality due to cardiovascular disease (2.48, 1.37 to 4.46), external injury or poisoning (3.25, 1.53 to 6.91), suicide (4.30, 1.74 to 10.61), respiratory disease (3.74, 1.40 to 9.99), and diseases of the digestive system (4.83, 1.77 to 13.21). The association of sexual abuse with premature mortality was stronger among women who smoked or had higher levels of anxiety during adulthood. Smoking, low physical activity, anxiety, and depression each explained 3.9-22.4% of the association between early life abuse and premature mortality. Conclusion: Early life physical and sexual abuse could be associated with a greater risk of adult premature mortality.